Genome-wide scan for selection signature and estimates of levels of autozygosity in Mangalarga Marchador horses - Santos, Wellington Bizarria dos [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The Brazilian Mangalarga Marchador horse has dominated the attention of many horse breeders for their gaited phenotype over decades. A particularity of this breed is its intermediate-speed gait known as "marcha" in Brazil, which is subdivided into “marcha batida” and “marcha picada”. Considering the few studies focused on the genetic improvement of the breed, with so many potentials for the economy of the country, the objective of this study was to analyze through molecular/genomic information, the occurrences of signatures of selection using different statistics, featuring runs of homozygosity and heterozygosity, as well as accessing the inbreeding levels by measurements of genomics coefficients, and based on pedigree. To achieve these objectives, 192 animals were genotyped using the platform: Axiom ® Equine Genotyping Array - 670.796 SNP (Thermo Fisher, USA). To study the selection signatures, three methods already established in the literature were used: Tajima’s D, Runs of Homozygosity (ROH) islands, and Integrated Haplotype Score (iHS). For the evaluation of inbreeding were investigated the characterization of Runs of Homozygosity (ROH) and Heterozygosity (ROHet), and genomics coefficients (FHOM, and FROH), and those based on Pedigree (FPED) were calculated. As a final result, our findings reveal evidence of signals of selection associated with athletic performance, gait type, and energy muscle activity. The other potential signatures were associated with energy metabolism, bronchodilator response, NADH regeneration, reproduction, keratinization, and immunological system. The observed inbreeding coefficients were considered low to moderate. For FROH the results were considered moderate (0.16). However, its levels were low in the method based on pedigree information (FPED) (0.008), as well as for the genomic method based on the differences between the observed and expected number of homozygous genotypes (FHOM) (0.010). Besides, the correlations between the inbreeding coefficients were also of low to moderate. The availability of high-density SNP chips made it possible to improve estimates of inbreeding coefficients. The calculation of FROH allowed access to information on the demographic history and genetic relationships in the population based on molecular information, and therefore estimates were higher than those observed in the classical approach.

Ao longo de décadas o cavalo brasileiro Mangalarga Marchador tem dominado a atenção de inúmeros criadores de cavalos pelo fenótipo marchador. Uma particularidade dessa raça é a marcha de velocidade intermediária, e que se subdivide em marcha batida e marcha picada. Considerando os poucos estudos voltados para o melhoramento genético da raça, com tantos potenciais para a economia do país, o objetivo deste trabalho foi analisar, por meio de informações moleculares/genômicas, as ocorrências de assinaturas de seleção com o uso de diferentes estatísticas, corridas de homozigosidade e heterozigosidade, bem como acessando os níveis de endogamia por medidas de coeficientes genômicos, e com base no pedigree. Para atingir os objetivos, 192 animais foram genotipados com o uso da plataforma: Axiom ® Equine Genotyping Array - 670.796 SNP (Thermo Fisher, EUA). Para estudar as assinaturas de seleção, três métodos estabelecidos na literatura foram utilizados: Tajima’ D, corridas de homozigose (“Runs of Homozygosity” - ROH) e escore de integração dos haplótipos (“Integrated Haplotype Score” - iHS). Para a avaliação da endogamia foi investigado as ROH e corridas de heterozigosidade (“Runs of Heterozygosity” - ROHet), além de coeficientes genômicos (FHOM, e FROH), bem como aqueles baseados no Pedigree (FPED). Como resultado final, revelamos evidências de assinaturas de seleção associadas ao desempenho atlético, tipo de marcha e energia para atividade muscular. As outras assinaturas potenciais foram associadas ao metabolismo energético, resposta ao broncodilatador, regeneração do NADH, reprodução, queratinização e sistema imunológico. Os coeficientes de endogamia calculados foram classificados de baixos a moderados. Para FROH os resultados foram considerados moderados (0,16). No entanto, seus níveis foram baixos no método baseado em informações de pedigree (FPED) (0,008), bem como no método genômico baseado nas diferenças entre o número observado e esperado de genótipos homozigotos (FHOM) (0,010). Além disso, as correlações entre os coeficientes de endogamia também foram de baixas a moderadas. A disponibilidade de chips SNP de alta densidade tornou possível melhorar as estimativas dos coeficientes de endogamia. O cálculo do FROH possibilitou o acesso a informações sobre a história demográfica e as relações genéticas da população com base em informações moleculares e, portanto, as estimativas foram superiores às observadas na abordagem clássica.
Genome-wide scan para assinatura de seleção e estimativas de níveis de autozigosidade em cavalos Mangalarga Marchador
Keywords: iHS; ROHet; ROH islands; FPED; Tajima’s D